Cardiac performance in hypertension re-evaluated through a combined haemodynamic ultrasonic method. Issue 3 (March 1980) - Fiorentini, C; Polese, A; Olivari, M T; Guazzi, M D
Abstract : From echocardiographic measurements, 39 patients with established, uncomplicated primary hypertension (diastolic pressure > 100 mmHg) were classified as follows: normal-sized heart (group 1, 10 cases); concentric left ventricular hypertrophy (group 2, 18 cases); left ventricular hypertrophy and cavity enlargement (group 3, 11 cases). Eighteen age-matched healthy subjects were investigated as a control group. Systolic and diastolic arterial pressure increased progressively from group 1 to 2 to 3. Left ventricular function, assessed from the relation between diastolic diameter and stroke index, was maintained in group 1, increased in group 2 (in spite of the greater pressure load), and reduced in group 3, in comparison with controls. Similarly, the mean velocity of circumferential fibre shortening (VCF) was normal in group 1, significantly increased in group 2, and reduced in group 3. It was impossible to discern whether the different behaviour of VCF in group 2 and in group 3 reflected opposite changes in ventricular contractility, or in wall stress during ejection, or in both. At variance with previous conclusions (which were based on utilisation of electrocardiographic and chest x-ray criteria to define hypertrophy) it is suggested that left ventricular concentric hypertrophy in man consequent to sustained hypertension is associated with an improved function. Whether this feature depends upon an augmented contractility or a ventricular unloading effect related to hypertrophy remains uncertain.